PENINGKATAN PENGETAHUAN IBU HAMIL TERHADAP ANEMIA DI PUSKESMAS KLARI : PENINGKATAN PENGETAHUAN IBU HAMIL TERHADAP ANEMIA DI PUSKESMAS KLARI - Kurniasih, Ari; Rachmy, Lina; Komala, Juwita (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2023)
Anemia is a condition when the number of red blood cells or the concentration of oxygen carriers in the blood Hemoglobin (Hb) is insufficient for the physiological needs of the body. The anemia most often found in pregnancy is anemia due to iron deficiency due to lack of iron intake in the diet. Impaired absorption, increased need for iron or due to too much iron coming out of the body. The distance of pregnancy is very influential on the incidence of anemia during pregnancy. Repeated pregnancies in a short time will deplete the mother's iron reserves. The purpose of this community service is to find out the level of knowledge of pregnant women about anemia that usually occurs during pregnancy in the Klari Health Center area. The activity was held on July 12 – 13, 2022 at Pusesmas Klari with 20 participants. To target the increase in knowledge of pregnant women about anemia, pre-test with an average value of 56 and post-test with an average value of 92.5. The activities are in the form of lectures and questions and answers, media used power points and leafets containing pictures accompanied by captions that can be understood by pregnant women. Maternal characteristic factors greatly affect the knowledge of pregnant women about anemia, therefore it is necessary to have activities such as classes for pregnant women to provide one of them about the prevention and treatment of anemia in pregnant women